Design of high impact thermal plastic polymer composites with balanced toughness and rigidity: Toughening with core-shell rubber modifier. (16th March 2020) - Li, Fushi; Gao, Yunbao; Zhang, Yue; Jiang, Wei
Abstract: It is different from one phase impact modifier such as ethylene-propylene rubber (EPR), ethylene-propylene-diene monomer copolymer (EPDM), polyolefin elastomer (POE) et al., that the core-shell rubber particles constructed by a hard core and a soft shell is a typical two phases impact modifier. They have been successfully and widely introduced to toughen polymers by melt blending or alloying in reactor. However, an important but unclear question is how to obtain the high impact thermal plastic polymer composites with less rigidity loss by optimizing the structure and the properties of the core and shell phases. To answer this question, we develop the model from one phase modifier to two phases modifier and make a quantitative calculation in this study and obtain the following results: (1) In order to obtain the high impact polymer composites with low rigidity loss, the modulus of the core should be as higher and the modulus of shell should be as lower as they can; (2) Comparing to one phase impact modifier, core-shell rubber particles toughened polymer composites can have less rigidity loss. The lowest modulus loss for the high impact PP can decrease from 26.1% for one phase modifier, to 13.5% for the core-shell modifier with PE core, and to 5.4% for the core-shell modifier with PP core; (3) The impurity, i.e. the rubber shell contains homo PP or PE and the core contains EPR, leads to the increase of the rigidity loss for the high impact PP alloys in reactor. Graphical abstract: Image 1 Highlights: A theory is given for minimizing rigidity loss in core-shell rubber particles toughened polymer composites. Core-shell rubber particles toughened polymer composites can have less rigidity loss than one phase impact modifier. Higher core modulus and lower shell modulus are more beneficial to increase the rigidity for toughened polymer composites. Improving the purity of EPR shell and PE or PP core can lower the rigidity loss for the high impact PP alloys in reactor. The lowest modulus loss for the high impact PP can reach to 5.4% for the core-shell modifier with PP core.